(untitled) (MAUSAM, 2004)
Canopy temperature and canopy-air temperature difference, leaf area index and other meteorological parameters were used to estimate the soil water content in irrigated as well as partially irrigated wheat. In case of bare-dry soil, the meteorological parameters only were used to estimate soil water content. The results showed clear shifts not only in accounting for variations in the water content at different depths but also in the predominant parameters for each of the three cases viz., irrigated, partially irrigated and bare-dry soil and also at different depths viz., 0-10, 0-20, 0-42.5 and 0-80 cm. A combination of net and reflected radiations with morning and afternoon mean soil temperatures were found the best predictors to estimate soil moisture under bare-dry soil. On the contrary, leaf area index was found the most predominant parameter for each of the four depths for estimation of soil water content under irrigated wheat. Canopy-air temperature difference and mean soil temperature at 1430 hours explained the maximum percent variation (67.64%) at 0-42.5 cm depth under irrigated wheat. Relative humidity along with either canopy temperature or net radiation were found the best predictors for the surface soil water content and accounted for 86.73% and 87.74% variation under partially irrigated soil. The results suggest that further improvement in the simulation of soil water content may result from the combination of canopy temperature, plant and environmental parameters particularly the energy balance and aerodynamic parameters.